Psychiatrists’ attitudes towards functional neurological disorders: results from a national survey - Marotta, Angela; Lasalvia, Antonio; Fiorio, Mirta; Zanalda, Enrico; Di Sciascio, Guido; Palumbo, Claudia; Papola, Davide; Barbui, Corrado; Tinazzi, Michele (Frontiers in Psychiatry, 2023)
Functional neurological disorder (FND) presents motor, sensory, and cognitive symptoms characterized by clinical signs incongruent with known neurological disease. Together with other health professionals, like neurologists, psychiatrists can play an essential role in diagnosing and managing these disorders. Hence, understanding their opinion and clinical experience with FND is of utmost importance to catch potential educational needs and improve healthcare services for patients. This study aims at assessing the knowledge, opinion, and clinical approach of Italian psychiatrists to FND. Members of the Italian Society of Psychiatry completed a 14-item web-based survey investigating their approach to FND. Results. Overall, 174 questionnaires were completed. Our main findings suggest that Italian psychiatrists have a psychogenetic conceptualization of FND. "Conversion disorders", in fact, is the term most frequently used by Italian psychiatrists to refer to FND, thus implying a psychological etiology of these disorders. Congruently with this view, psychotherapy associated with pharmacological therapy is considered the most appropriate treatment by psychiatrists, while physiotherapy is an under-recognized treatment option for FND. The present study highlights that a psychogenetic view of FND dominates among Italian psychiatrists. This could be due to out-ofdate knowledge about the pathophysiology of this group of disorders. Promoting education about novel approaches to FND would be of crucial importance to improving care for patients suffering from this condition.